Fostering Agentic Engagement: Working toward Empowerment and Equity through Pedagogical Partnership - Alison Cook-Sather (Georgia Southern University, 2021)
An established body of research details the faculty role in promoting student engagement. Newer scholarship on agentic engagement foregrounds student-initiated engagement in classroom learning. Our SoTL project explored how participating in student-faculty pedagogical partnerships supported two undergraduate students in expanding agentic engagement to encompass student empowerment and equity both within and beyond the classroom. We draw on the students’ autoethnographic accounts of three interrelated experiences: (1) joining a pedagogical partnership program as pedagogical consultants and developing confidence in, capacity for, and commitment to supporting student and faculty learning; (2) carrying that confidence, capacity, and commitment into the courses in which those students were enrolled to enact agentic engagement in their own and in support of others’ learning; and (3) expanding the agentic engagement they developed in the first two instances beyond classroom learning. This study has implications for classroom instruction, faculty professional development, and student advising and retention.